Treating complex trauma in adolescents and young adults - Briere, John (Sage, 2012)
"This book, while conceived as a professional volume, can be used in a variety of courses. This book covers areas such as symptoms of trauma, how to assess and plan treatment, how to educate adolescents about their trauma, and how to intervene with family and in group therapy. It contains a variety of cases for illustrative purposes"--Provided by publisher